BDNF/TRKB/P75NTR polymorphisms and their consequences on antidepressant efficacy in depressed patients. (June 2015) - Colle, Romain; Deflesselle, Eric; Martin, Séverine; David, Denis J; Hardy, Patrick; Taranu, Adéla; Falissard, Bruno; Verstuyft, Céline; Corruble, Emmanuelle
We propose an extensive review of the literature about BDNF/TRKB/P75NTR polymorphisms and their consequences on antidepressant efficacy in depressed patients. Five genome-wide association studies and 30 association studies were included. Twenty seven studies focused on the Val66Met polymorphism (rs6265), the Met allele being associated with a higher antidepressant efficacy only in Asian patients. Other BDNF/TRKB/P75NTR polymorphisms ( BDNF : rs7103411, rs7124442, rs908867, rs2049046, rs61888800, rs10501087, rs1491850; TRKB : rs10868223, rs11140778, rs1565445, rs1659412; P75NTR : rs2072446) were reported to be associated with antidepressant efficacy but these results were not replicated. Finally, there are 15 positive studies among 30 studies regarding BDNF/TRKB/P75NTR polymorphisms. The only SNP which benefits of at least three positive studies is the BDNF Val66Met polymorphism (rs6265). Consequently, with a lack of good and consistent studies, the clinical utility of BDNF in treatment selection is far from clear. We propose several recommendations for further studies.